1999
DOI: 10.1159/000006631
|View full text |Cite
|
Sign up to set email alerts
|

Relative Medial and Dorsal Cortex Volume in Relation to Foraging Ecology in Congeneric Lizards

Abstract: The need to locate distributed resources such as mates, food, and nests is correlated with an enlarged hippocampus in many mammalian and avian species. This correlation is believed to be a consequence of selection for spatial ability. Little is known about how such ecological needs affect non-mammalian, non-avian species. In lizards, the putative hippocampal homologues are the dorsal cortex (DC) and medial cortex (MC). We examined the relationship between foraging ecology and the size of the DC and MC in conge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 63 publications
2
8
0
Order By: Relevance
“…; Baird Day et al . ). Similarly, animals with larger brains, for example mammals, have a greater degree of behavioural flexibility and are better able to successfully colonise new environments (Sol et al .…”
Section: Spatial Use Properties and Their Consequences For Pairwise Tmentioning
confidence: 97%
“…; Baird Day et al . ). Similarly, animals with larger brains, for example mammals, have a greater degree of behavioural flexibility and are better able to successfully colonise new environments (Sol et al .…”
Section: Spatial Use Properties and Their Consequences For Pairwise Tmentioning
confidence: 97%
“…Brain composition is associated with ecological niche occupation and behavioural capacities in mammals [16], birds [17,18] and fishes [19][20][21]. Residual variation in discrete brain regions is correlated with specific sensory [22][23][24][25][26][27], motor [28][29][30] and cognitive abilities [31][32][33], including from artificial selection [34,35]. Therefore, according to the mosaic model, selection for specific behaviours targets genes that specify characteristics of their underlying brain modules, such as numbers of neurons or intra-and inter-region connectivity [36], and variation in brain composition results from accretion of many isolated changes.…”
Section: Introductionmentioning
confidence: 99%
“…Day et al found that active forgers that presumably have increased demands on spatial processing abilities also have larger relative dorsal and medial cortices compared to sit and wait predators. Interestingly, their previous study found no difference between the two species on a spatial memory task, suggesting that differential spatial memory abilities may not underlie the relationship between foraging strategy and the cortices . Spatial area use may be another factor that can influence spatial processing and the brain; male cottonmouth snakes traverse a greater area than do females, and have larger medial cortices .…”
Section: Integrating Behavior and Mechanism Enhances Our Understandinmentioning
confidence: 91%
“…Interestingly, their previous study found no difference between the two species on a spatial memory task, suggesting that differential spatial memory abilities may not underlie the relationship between foraging strategy and the cortices. [77] Spatial area use may be another factor that can influence spatial processing and the brain; male cottonmouth snakes traverse a greater area than do females, and have larger medial cortices. [78] Similarly, in male sideblotched lizards, increased spatial area use within the context of territoriality correlates with increased DC volume.…”
Section: Correlative Studies Of Neuroanatomy Imply Cognitive Parity Amentioning
confidence: 99%